2005
DOI: 10.1073/pnas.0409559102
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids induce cholera toxin expression in Vibrio cholerae in a ToxT-independent manner

Abstract: The production of cholera toxin (CT) during Vibrio cholerae infection results in the hallmark diarrhea that characterizes the disease cholera. The transmembrane protein ToxR was originally identified as a functional transcriptional activator of ctxAB in a heterologous Escherichia coli system. However, direct ToxR activation of the ctxAB promoter in V. cholerae has not been previously demonstrated. Instead, a regulatory cascade has been defined in which the activators ToxRS and TcpPH modulate ctxAB expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
128
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 45 publications
(46 reference statements)
2
128
1
Order By: Relevance
“…Bile salts have previously been implicated in virulence in Vibrio parahaemolyticus (19), but the mechanism of induction is unclear. Interestingly, it has been shown that in a classical strain of V. cholerae (20), bile salts also may affect ToxR activity to enhance ctx production independent of ToxT. Although the induction in this case was rather minimal compared with the maximal ctx expression, it does suggest that bile salts may play additional roles in regulating virulence.…”
Section: Discussionmentioning
confidence: 62%
“…Bile salts have previously been implicated in virulence in Vibrio parahaemolyticus (19), but the mechanism of induction is unclear. Interestingly, it has been shown that in a classical strain of V. cholerae (20), bile salts also may affect ToxR activity to enhance ctx production independent of ToxT. Although the induction in this case was rather minimal compared with the maximal ctx expression, it does suggest that bile salts may play additional roles in regulating virulence.…”
Section: Discussionmentioning
confidence: 62%
“…2 These two proteins play a major role in controlling the production of virulence factors, such as cholera toxin; in addition, ToxR controls the expression of the two general diffusion porin genes ompU and ompT. [3][4][5][6][7] Once inside the host, the activation of ToxR is believed to turn on ompU expression while repressing ompT expression. Although OmpU and OmpT are not required for virulence, 8 the type of porin present in the outer membrane may have an impact on the ability of V. cholerae to colonize the duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…ToxR contains a single transmembrane ␣-helix separating a cytoplasmic DNA-binding domain from a short C-terminal periplasmic domain (10). A role in signal transduction by ToxR may be likely in the presence of bile salts, where it regulates cholera toxin production (12) and expression of the outer membrane porins OmpU and OmpT (13).…”
mentioning
confidence: 99%